Thyroid Function in Children with Idiopathic Nephrotic Syndrome - Das, Aparup Kanti; Barua, Tanuka; Dey, Dipika; Roy, Minakshi; Choudhury, Zabeen; Karim, Mohammed Rezaul (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2020)
Background: The underlying abnormality in nephrotic syndrome is an increase inpermeability of the glomerular membrane. Urinary loses of binding proteins such asThyroxine Binding Globulin (TBG) albumin results in a reduction in serumthyroxine(T4) and sometimes in total T3 levels. The study was done to assess thyroidhormone status of idiopathic nephrotic syndrome patients at diagnosis, comparethe thyroid function after treatment with steroid, correlate with serum albumin andcompare the thyroid function with control group. Materials and methods: It was an analytic type of cross sectional study, done inPaediatric ward, Chittagong Medical College Hospital, Chattogram from 01.05.11 to30.11.11. Total 58 patients in two groups were included. In group A 32 cases ofidiopathic nephrotic syndrome patients and in group B 26 control cases of same ageand sex were taken. In group A thyroid function was done at initial diagnosis and inhypothyroid patients in this group again thyroid function was done after treatmentwith steroid. Data was collected through interviewing with pre-designedquestionnaire, physical examination and investigation techniques. Results: Thyroid hormone level of nephrotic children were significantly lower thanthat of control group. Nephrotic children with thyroid hypofunction were foundeuthyroid after initial treatment with steroid that was statistically significant andthere was positive correlation between serum albumin and thyroid hormone level. Conclusion: Children suffering from nephrotic syndrome had significant thyroidhypofunction because of low serum albumin level and after treatment with steroidthey became euthyroid. Chatt Maa Shi Hosp Med Coll J; Vol.19 (1); January 2020; Page 51-54